Long-range correlations in the mechanics of small DNA circles under topological stress revealed by multi-scale simulation - Sutthibutpong, Thana; Matek, Christian; Benham, Craig; Slade, Gabriel G. [UNESP]; Noy, Agnes; Laughton, Charles; Doye, Jonathan P. K.; Louis, Ard A.; Harris, Sarah A. (Oxford Univ Press, 2016)
It is well established that gene regulation can be achieved through activator and repressor proteins that bind to DNA and switch particular genes on or off, and that complex metabolic networks determine the levels of transcription of a given gene at a given time. Using three complementary computational techniques to study the sequence-dependence of DNA denaturation within DNA minicircles, we have observed that whenever the ends of the DNA are constrained, information can be transferred over long distances directly by the transmission of mechanical stress through the DNA itself, without any requirement for external signalling factors. Our models combine atomistic molecular dynamics (MD) with coarse-grained simulations and statistical mechanical calculations to span three distinct spatial resolutions and timescale regimes. While they give a consensus view of the non-locality of sequence-dependent denaturation in highly bent and supercoiled DNA loops, each also reveals a unique aspect of long-range informational transfer that occurs as a result of restraining the DNA within the closed loop of the minicircles.